1961
DOI: 10.1080/09553006114550071
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of Oogonia and Oocytes in the Foetal Rat

Abstract: Pregnant rats were exposed to doses of 25 to 2x 100 r of x-rays at varying times between the 13th and the 20th days after insemination. Female offspring were killed at 25 clays post partum, and the number of ,oocytes was estimated from serial sections of the ovaries.The population of oocytes in the irradiated ovaries was found to depend both on the dose of x-rays administered and on foetal age at the time of exposure.The period of maximum radiosensitivity, which occurred on the 15th day of gestation, was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1966
1966
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…If depletion of PGCs was not compensated through extra proliferation of oogonia, this must result in fewer oocytes in the ovary. Studies investigating the exposure of female rat fetuses to low doses of radiation [31] or busulfan [32] have shown that the ovary is sensitive to these agents between E13.5 and 17.5. Hence, it is likely that the ovary will be sensitive to CP throughout the latter half of fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…If depletion of PGCs was not compensated through extra proliferation of oogonia, this must result in fewer oocytes in the ovary. Studies investigating the exposure of female rat fetuses to low doses of radiation [31] or busulfan [32] have shown that the ovary is sensitive to these agents between E13.5 and 17.5. Hence, it is likely that the ovary will be sensitive to CP throughout the latter half of fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Of the limited number of studies designed to test the ability of the prenatal mammalian female germ cell to survive an exposure to ionizing radiation, the works of Beaumont (1961Beaumont ( , 1962 are probably the most thorough. She inter¬ preted the response of the prenatal rat through counts of oocytes surviving to 25 days post partum and found that 100 R of X-rays inflicted negligible damage to the germ-cell population prior to Day 15 of gestation, but radiation administered at Day 15 reduced oocyte numbers to 15% of control values.…”
Section: Radio-response Of the Prenatal Bovine Ovarymentioning
confidence: 99%
“…Beaumont [2,3] investigated sensitivity of germ cells to X-irradiation at various stages of ovarian development in rats and found that the radiosensitivity was the highest on the 15th day of intra-uterine life, and then shortly after birth.…”
Section: Discussionmentioning
confidence: 99%